VP197 Sustainable Production Of Rapid Health Technology Assessments And Clinical Guidelines. (12th January 2018) - Thompson, Lorna; Myles, Susan; Macpherson, Karen
Abstract : INTRODUCTION: With increasing resource pressures on health systems, rapid developments in innovative technologies and limited numbers of skilled assessors, there is a need to establish sustainable methods to provide advice on healthcare technologies for decision makers. The European Network for Health Technology Assessment (EUnetHTA) has been testing an approach of collaborative production of rapid Health Technology Assessments (HTAs) and adaptation of these locally. The Scottish Health Technologies Group (SHTG) participated in two collaborative and adaptation projects to test whether this could save time and resource, whilst providing a product as robust and relevant as if developed locally. Concurrently the Scottish Intercollegiate Guidelines Network (SIGN) has been exploring ways to develop clinical guidelines more efficiently, including the use of rapid HTAs to inform recommendations. METHODS: Having established the relevance of the topics to NHS Scotland, SHTG participated as peer reviewers for EUnetHTA reviews on mitral valve repair and mechanical thrombectomy. On completion, SHTG summarized their content to fit with the well-accepted rapid review report format used in Scotland. Content was supplemented with a review of economic evidence, currently not included in the European reports, local epidemiological information and recently published studies. The thrombectomy report and associated Advice Statement were used by a small expert group to update a SIGN clinical guideline recommendation. RESULTS: Providing advice through adaptation proved feasible and acceptable to stakeholders. Limited time was saved because of the supplementary work undertaken, and lessons have been learned about what should and should not be done in future .The guideline recommendation was updated and made available more quickly than similar previous updates. CONCLUSIONS: Further such collaborations and adaptations will be pursued as this appears to be a sustainable approach for the future. The process could be aided by EUnetHTA publishing forward work plans and also by the inclusion of economic information, with details of the decision-making context provided, to allow assessment of its relevance locally.